Fabrication of custom made ocular prosthesis with three different impression techniques: a report of four cases - Y. Rao; P. Yadav; M. D'souza; J. Singh; D. Patel (Nigerian Dental Association, 2014)
Loss of eye has a bad effect on the psychology of the patient. Eye prosthesis is fabricated to regain the patient's confidence by meticulous replacement of the missing eye. Immediate fitting of an anophthalmic socket with an artificial eye may not always be possible, and a delayed prosthesis delivery may result in settling and sinking of the prosthesis into the socket, therefore requiring orbital cavity conformation. It becomes a challenging task for a maxillofacial prosthodontist to fabricate a prosthesis that replicates the healthy side of the face. This article presents a short review of three functional ocular impression techniques to achieve a better fit of the prosthesis to the defect area. These techniques aim to combine cosmetic excellence with comfort for greater benefit to the patients.